1984
DOI: 10.1002/aheh.19840120507
|View full text |Cite
|
Sign up to set email alerts
|

Zur Analytik von Chlorphenoxyalkansäuren und Chlorphenolen. Teil 2: Nachweis von Chlorphenoxyalkansäuren und Chlorphenolen in der Fischgalle

Abstract: S"um/nary: The bile liquid is preserved with ethanol and the protein is precipitated. Prefractionating is done by liquid-liquid Pxtraction by chloroform and ethyl aceta.t,e. The extra& are eo-1 nmn-chromatographically separated on Florisil and subsequently detect,ed by t hin-layer chromatography. For determining the identit,g of substances, the penta fluorobenzyl derivatives are prepared and chromatographed under the same conditions. Detection is carried out. with the aid of aiiinioiiiacal silver nitrate reage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…But with the detection of carcinogenous properties of 2,4,6-trichlorophenol (NCI, 1979) and of embryotoxic and teratogenic properties of pentachlorophenol (Schwetz et al, 1978(Schwetz et al, , 1974) the health-related effects of these substances-not only within working areas-caused a drastically rising interest in them. Furthermore, the progress in analytics of substituted phenols and their increasing detection in the environment (Abrahamson et al, 1983;Bio et al, 1983;Buckman et al, 1984;Grahl et al, 1984;Korhonen et al, 1983;Lee et al, 1984;Onodera et al, 1984;Renberg, 1983;Rennie, 1982;Seefeld et al, 1983;Thielemann, 1983) were closely linked. Many authors reported on the detection in drinking water (Burnham et al, 1972;Sorensen, 1978;Thielemann, 1970;Chriswell et al, 1975;Dietz and Traud 1978a;Grob, 1973).…”
Section: Introductionmentioning
confidence: 95%
“…But with the detection of carcinogenous properties of 2,4,6-trichlorophenol (NCI, 1979) and of embryotoxic and teratogenic properties of pentachlorophenol (Schwetz et al, 1978(Schwetz et al, , 1974) the health-related effects of these substances-not only within working areas-caused a drastically rising interest in them. Furthermore, the progress in analytics of substituted phenols and their increasing detection in the environment (Abrahamson et al, 1983;Bio et al, 1983;Buckman et al, 1984;Grahl et al, 1984;Korhonen et al, 1983;Lee et al, 1984;Onodera et al, 1984;Renberg, 1983;Rennie, 1982;Seefeld et al, 1983;Thielemann, 1983) were closely linked. Many authors reported on the detection in drinking water (Burnham et al, 1972;Sorensen, 1978;Thielemann, 1970;Chriswell et al, 1975;Dietz and Traud 1978a;Grob, 1973).…”
Section: Introductionmentioning
confidence: 95%